2013
DOI: 10.1002/clc.22171
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy and Cost‐Effectiveness of a Pocket‐Sized Transthoracic Echocardiographic Imaging Device

Abstract: This study demonstrates that the pocket-sized pTTE provides accurate detection of cardiac structural and functional abnormalities beyond the ECG. In addition, the use of pTTE as an initial screening tool prior to sTTE is cost-effective, suggesting that the pocket-sized pTTE is poised to alter the current diagnostic strategy in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…Previous studies reported that the use of pocket-size ultrasound devices was associated with a 20–30% cost reduction in healthcare costs9 15–20 Nevertheless, most reported studies were conducted by experts. It has been suggested that internist may be able to use these hand-held devices after a limited training period 21–24.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the use of pocket-size ultrasound devices was associated with a 20–30% cost reduction in healthcare costs9 15–20 Nevertheless, most reported studies were conducted by experts. It has been suggested that internist may be able to use these hand-held devices after a limited training period 21–24.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the cost-effectiveness of the pocket-echo for screening various cardiac diseases has been reported. 21 Dijos et al showed an excellent correlation between the abdominal aortic diameter determined by standard echocardiography and the pocket-echo, resulting in 100% agreement for the AAA diagnosis. 22 Considering the portability and low cost of pocket-sized imaging devices, similar to stethoscopes, the pocket-echo may alter the current screening strategies for AAA by providing a supplement to physical examination.…”
Section: Prevalence and Determinants Of Aaamentioning
confidence: 96%
“…In everyday clinical practice pocket-size devices could complement the physical examination in outreach clinics and in intensive care units; they may serve as a tool for fast initial cardiac assessment in emergency units, during cardiologic counseling, in ambulances and for screening programs in schools and industries [7]. Moreover, miniaturized echo systems allow improvement of the cost-effectiveness of the service provided by the echo-lab for inpatients and avoid patients' discomfort derived from prolonged waiting time [20,21]. The main limitation of these devices is represented by poor image quality linked to the type of machine used and to the operator experience.…”
Section: Discussionmentioning
confidence: 99%